2016
DOI: 10.1080/00288233.2016.1188132
|View full text |Cite
|
Sign up to set email alerts
|

Mineral elements in grasses growing in contrasting environmental conditions in southern Patagonia

Abstract: The importance of grasses and graminoids for sheep nutrition in Argentinian Patagonia is widely recognized. Focusing on sheep nutrition, we assessed the concentration of mineral elements in grasses growing in three ecological areas of southern Patagonia, representing a vegetation and climate gradient. With the aim of establishing potential relationships, tissue concentrations of several essential and non-essential elements for plants were determined; soil properties were also analysed. Soil and plant tissue mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
3
1
2
Order By: Relevance
“…Similarly, the trace elements evaluated (Al, Li, Pb, Rb, Sr, Ti, and Tl) were below the concentration range considered toxic for plants (e.g., Kabata-Pendias, 2011). Compared to the results by Bahamonde et al (2016b) the concentrations in N. antarctica mature leaves evaluated here were higher for Al, Sr, and Ti, lower for Rb, and similar for Pb. It must be noted that some of such trace elements may replace the role of some essential nutrients, like e.g., Rb with K (Nyholm and Tyler, 2000), or Li and Sr with Ca (Shahzad et al, 2016; Sasmaz and Sasmaz, 2017).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Similarly, the trace elements evaluated (Al, Li, Pb, Rb, Sr, Ti, and Tl) were below the concentration range considered toxic for plants (e.g., Kabata-Pendias, 2011). Compared to the results by Bahamonde et al (2016b) the concentrations in N. antarctica mature leaves evaluated here were higher for Al, Sr, and Ti, lower for Rb, and similar for Pb. It must be noted that some of such trace elements may replace the role of some essential nutrients, like e.g., Rb with K (Nyholm and Tyler, 2000), or Li and Sr with Ca (Shahzad et al, 2016; Sasmaz and Sasmaz, 2017).…”
Section: Discussioncontrasting
confidence: 71%
“…For both species, the only exception was leaf Fe in the lower productivity sites (MPS and LPS), with concentrations below optimal threshold values (Lambers et al, 2008; Kirkby 2012). In the only reported data set of foliar micronutrient and trace element concentrations in this region, Bahamonde et al (2016b) evaluated grasses growing in N. antarctica forests at similar dates during the growing season. Comparing with these grass tissue data, the concentrations measured for N. antarctica mature leaves were higher for B, and Zn, and similar for Cu, Mn, and Ni.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrated that yak meat source can be discriminated at a much smaller scale, ie between regions within The mineral composition of meat is influenced by the environment [22] and the geological processes which influence the soil profile. There was a research demonstrated the environmental influence and geographical variation in mineral content of pastures grown in extensive grassland regions of southern Patagonia [26] . In this research the soil characteristics differed markedly among the three Counties [27] .…”
Section: Discussionmentioning
confidence: 99%
“…La única excepción en ambas especies fue la concentración de Fe en hojas de los sitios de menor productividad (CSM y CSB), con concentraciones por debajo de lo considerado valores óptimos (Lambers et al 2008, Kirkby 2012. En la única publicación con datos de concentración de micro-nutrientes y elementos traza en la región patagónica, Bahamonde et al (2016c) evaluaron gramíneas creciendo en el sotobosque de N. antarctica en fechas similares a las de este estudio durante la estación de crecimiento. Comparados con esos datos, las concentraciones en hojas maduras de ñire evaluadas aquí fueron más altas para B y Zn, mientras que fueron similares para Cu, Mn y Ni.…”
Section: Concentración Y Reabsorción De Micro-nutrientes Y Elementos Trazaunclassified
“…Los valores de reabsorción de Cu, Li y Ni estuvieron positivamente correlacionados con sus concentraciones en hojas maduras, lo cual es consistente conKillingbeck y Costigan (1988), quienes publicaron valores de reabsorción similares de estos elementos.Similarmente, los elementos traza evaluados (Al, Li, Pb, Rb, Sr, Ti y Tl) presentaron concentraciones por debajo de los rangos considerados como tóxicos en la literatura especializada (Kabata-Pendias 2011). En comparación con los resultados publicados porBahamonde et al (2016c) las concentraciones en hojas maduras de N. antarctica evaluadas aquí fueron más altas para Al, Sr y Ti, más bajas para Rb y similares para Pb.Un aspecto a tener en cuenta es que algunos elementos traza pueden reemplazar el rol de algunos nutrientes esenciales, tales como el Rb con el K(Nyholm y Tyler 2000), o el Li y Sr reemplazando el Ca(Shahzad et al 2016, Sasmaz y Sasmaz 2017. Los resultados obtenidos en este estudio por ejemplo para Rb mostraron una tasa de reabsorción similar al K, lo cual coincide con otros estudios de movilidad de este elemento (por ejemplo, Nyholm y Tyler 2000).Respecto a la tasa de reabsorción de algunos elementos traza, Al y Ti fueron inmovilizados en hojas sin reabsorción en ningún sitio ni especie.…”
unclassified